Sporoderm-Broken Spores of Ganoderma lucidum Sensitizes Ovarian Cancer to Cisplatin by ROS/ERK Signaling and Attenuates Chemotherapy-Related Toxicity - Cen, Kaili; Chen, Ming; He, Mengye; Li, Zhenhao; Song, Yinjing; Liu, Pu; Jiang, Qi; Xu, Suzhen; Jia, Yunlu; Shen, Peng (Frontiers in Pharmacology, 2022)
Platinum-based chemotherapeutics as cisplatin are the cornerstone of treatment for ovarian cancer in clinic practice, while the clinical efficacy of cisplatin is profoundly limited due to chemoresistance and severe adverse effects. Sporoderm-broken spores of Ganoderma lucidum (SBSGL) has been reported to possess anti-tumor effects. However, the function and mechanism of SBSGL and its essential composition ganoderic acid D (GAD) in the efficacy of cisplatin therapy in ovarian cancer have yet to be investigated. Here, we investigated the combined effect of SBSGL and cisplatin in ovarian tumor xenograft. The results showed that combining SBSGL with cisplatin reduced tumor growth and ameliorated cisplatin-induced intestinal injury and myelosuppression. We also confirmed that GAD could enhance the efficacy of cisplatin in SKOV3 and cisplatin-resistant SKOV3/DDP cells and the combination of GAD and cisplatin induced cytotoxicity by increasing the intracellular reactive oxygen species (ROS). Mechanistically, we proved that ROS-mediated ERK signaling inhibition played an important role in the chemo-sensitization effect of GAD on ovarian cancer. Taken together, combining SBSGL with cisplatin provides a potential strategy against ovarian cancer.